Review of various techniques of small bowel transplantation in pigs - Weih, Sandra; Kessler, Markus; Fonouni, Hamidreza; Golriz, Mohammad; Nickkholgh, Arash; Schmidt, Jan; Holland-Cunz, Stefan; Mehrabi, Arianeb (Journal of surgical research, 2011)
Because of anatomical and physiological similarities to humans, porcine small bowel transplantation (SBTx) can be used as an appropriate experimental model in the field of surgical research. Various approaches to SBTx have been described in literature. The aim of this work is to present a review of different surgical techniques of SBTx which have been developed using the porcine model. Our analysis of Medline-cited studies dealing with different techniques of SBTx in porcine models was particularly focused on surgical aspects. With regard to graft procurement and enterectomy, the reported techniques vary widely. Arterial reconstruction is mainly conducted by performing the anastomosis between the superior mesenteric artery (SMA) of the donor and SMA or infrarenal aorta of the recipient. Alternatively, an aortic segment of the donor can be anastomosed to the infrarenal aorta of the recipient. Venous anastomosis is frequently performed between the superior mesenteric vein (SMV) of the donor and SMV or the inferior vena cava (IVC) of the recipient. Some studies also report venous anastomosis between the portal vein of the donor and the recipient. Bowel continuity is then restored by end-to-end or end-to-side anastomosis. Remarkable results were generated thanks to improved techniques which include proximal side-to-side ileo-ileal anastomosis with double-barrel ileostomy, or so-called “Paul-Mikulicz-Ileostomy”. Most frequently used were jejunostomy and the “Bishop-Koop-Ileostomy” - where the proximal part of the bowel is anastomosed end-to-side to the distal part, which is then exteriorized as an ostomy. Based on the techniques presented in this review, one must select the most suitable surgical technique of porcine SBTx among those various models.
Gesehen am 14.11.2022